Women's Authority in Patriarchal Social Movements: The Case of Female Salafi Preachers. Issue 1 (9th August 2019) - Nielsen, Richard A.
Abstract: How do women gain authority in the public sphere, especially in contexts where patriarchal norms are prevalent? I argue that the leaders of patriarchal social movements face pragmatic incentives to expand women's authority roles when seeking new movement members. Women authorities help patriarchal movements by making persuasive, identity‐based arguments in favor of patriarchy that men cannot, and by reaching new audiences that men cannot. I support this argument by examining the rise of online female preachers in the Islamist Salafi movement, using interviews, Twitter analysis, and automated text analysis of 21, 000 texts by 172 men and 43 women on the Salafi‐oriented website saaid.net. To show the theory's generality, I also apply it to the contemporary white nationalist movement in the United States. The findings illustrate how movements that aggressively enforce traditional gender roles for participants can nevertheless increase female authority for pragmatic political reasons.